A STUDY ON STUDENTS’ OBSTACLES IN MASTERING VOCABULARY AT SMK AL IMAM JEMBER - Agus Hani Wafi (Language-Edu, 2021)
Vocabulary is the basic language element, which has crucial role in language learning. Whereas the book is mostly in English, some students get difficulties in mastering vocabulary.  This research aims to know the kinds of students’ obstacles in mastering vocabulary. This research is descriptive qualitative which explains the phenomena systematically, factually and accurately by interview and observation. The subject are eleventh grade students at SMK Al-Imam Jember. The result is explained in the form of describing words, and it is presented in narrative. Based on the result, the students of SMK Al Imam Jember had six obstacles in mastering vocabulary and seven causes the students’ difficulties in mastering vocabulary. Moreover, students’ learning could be affected by internal and external factor. Internal factor consist of physic and psychological aspect. While for external factor, consists of social environment and nonsocial environment. Those factors caused by the students rarely use English as mean of communication and never write and learn new vocabulary during learning or in their daily activities.